Efficient Utilization and Optimal Allocation of Agricultural Water Resources in the Yellow River Basin - Zhao Ying; Wang Haixia; Wang Yi; Niu Zhongen; Hu Qiuli; Zhao Fen; Suo Lizhu; Xu Zhenghe; Chen Xiaobing (中国工程科学, 2023)
Water resources are basic natural and economic resources of strategic significance and are vital for the high-quality agricultural development and ecological protection of the Yellow River Basin. To implement the national strategy of ecological protection and high-quality development in the Yellow River Basin, it is significant to improve the use efficiency and allocation of water resources in the basin. This study focuses on the high-efficiency utilization and sustainable development of agricultural water resources, adopts the research methods of systematic hydrology, and adheres to an all-encompassing approach to food. Based on the theories and technologies for the optimal allocation of water resources in the process of high-quality agricultural development, it explores the mechanism for the hydrologic process of farmlands and investigates the challenges faced in terms of water use efficiency improvement, optimal allocation of agricultural and ecological water resources, collaborative optimization of water, food, and ecosystem, and construction of farmland information systems. Countermeasures are further proposed. This study reviews the agricultural water-saving and water resource allocation capabilities of the whole Yellow River Basin from a water cycle perspective and is expected to provide basic support for the optimal allocation of land and water resources, high-quality agricultural development, and ecological protection collaboration in the Yellow River Basin.